2019
DOI: 10.1063/1.5096879
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced anisotropy and study of magnetization reversal in Co/C60 bilayer thin film

Abstract: The interface between the organic semiconductor (OSC)/ferromagnetic (FM) material can exhibit ferromagnetism due to their orbital hybridization. Charge/spin transfer may occur from the FM to OSC layer leading to the formation of “spinterface,” i.e., the interface exhibiting a finite magnetic moment. In this work, the magnetic properties of the Co/C60 bilayer thin film have been studied to probe the interface between the Co and C60 layer. Polarized neutron reflectivity (PNR) measurement indicates that the thick… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…This in-dicates the hardening the pinning of out-of-plane magnetization due to strong adsorption of C 60 on Co-substrate. In our previous study on Co-C 60 in-plane system, we have also seen that introducing a C 60 layer anisotropy of system has been increased [23].…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…This in-dicates the hardening the pinning of out-of-plane magnetization due to strong adsorption of C 60 on Co-substrate. In our previous study on Co-C 60 in-plane system, we have also seen that introducing a C 60 layer anisotropy of system has been increased [23].…”
mentioning
confidence: 84%
“…Similarly, for C 60 deposited on a polycrystalline Fe films also exhibited spinterface and domain size was reduced [22]. Further in another study we have shown that the spinterface in a Co/C 60 system has similar effect, however the anisotropy increased due to the spinterface [23]. Although there have been a few works on in-plane magnetized films however the study of such spinterface on domains in a perpendicularly magnetized films are scarce.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Surprisingly, not only the spin polarization but also the magnetic anisotropy has been found deeply modified at the molecule/ferromagnet interface. For example, the C p z -Co d z 2 hybridization has been demonstrated to be at the origin of an enhanced perpendicular anisotropy at the C 60 /Co(0001) interface [7,8], which induces a magnetic hardening in either out-of-plane [9] or in-plane magnetized samples [10]. The link between magnetic properties and the fine details of the interface structure has not been studied extensively up to now for such samples even if few experimental evidences have been reported, either on the magnetic [11] or the transport properties [12].…”
Section: Introductionmentioning
confidence: 99%
“…C 60 can exhibit ferromagnetism at the interface (known as spinterface) when it is deposited on any ferromagnet 21,22 . Presence of C 60 can modify the magnetic property of the ferromagnetic materials as well as nonmagnetic metal [23][24][25][26][27][28] . However, the low value of SOC in OSC limits them for efficient spin to charge conversion.…”
mentioning
confidence: 99%